The Influence of Internal Audit on the Quality of Financial Statements: Survey on Private Sector Manufacturing Companies in Bandung - Maulana Yusup; Djajun Juhara (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
The quality of financial reports is one of the critical aspects for capital owners in assessing the company's success in its business. Previous research has shown a positive relationship between internal audits and the presentation of quality financial statements. Based on the critical role of the presentation of financial statements, the researchers researched the influence of internal audits on the quality of financial statements. The researcher uses a quantitative approach in answering the problem formulation that set. The sample in this study were 59 employees of the audit department in two manufacturing companies in the city of Bandung. Data analysis used simple linear regression with the results showing a positive influence of internal audit on the quality of financial reports by 50.5%. In contrast, the rest was influenced by other factors not examined. The study results indicate that the better the internal audit is carried out, the better the quality of financial reports.